Interpretación petrogenética del gabro de tragarepas al norte de pacho - cundinamarca, colombia (2002)
Close to the Pacho town it is exposed a basic intrusive body of conic morphology, named as Gabbro Tragarepas intruding sedimentary rocks of Albian age. Petrographically intrusive rocks are composed of plagioclase labradorite, augite and hornblende, classified as piroxenic, hornblendic gabbros; presents both granular and inter-granular and ofitic- subofitic textures. Also it is common to find hornblende, chlorite, calcite, epidote and pyrite as secondary minerals, formed by hydrothermal alteration, event recognized on all intrusive body. Geochemistry characterization shows that the gabbroic body belongs to sub-alkaline series with sodic tendency and tholeiitic character, which permits to classify the intrusive body as gabbro, gabbrodiorite and diorite with low alkalis.  Tectonic discrimination diagrams were useful to establish the generation of the intrusive body by an intraplate distensive domain, as a consequence of the high basin's subsidence along the actual area of the Colombia Eastern Mountain Range during great part of the Mesozoic. The thickness of the continental crust originated deeper faults through which the magma rises from the mantle partial fusion.  The petrographic and geochemistry results obteined from this work, show a great similarity with the other gabbroic bodies on the Eastern Mountain Range. Perhaps, they were emplaced along the same magmatic event.